ANALISIS KEMISKINAN ANAK BALITA PADA RUMAH TANGGA DI PROVINSI SUMATERA BARAT - Nasri Bachtiar; Mora J Rasbi; Rahmi Fahmi (Jurnal Kependudukan Indonesia, 2016)
The purpose of this study is to analyze factors that influence children poverty in West Sumatera Province based on household and parents characteristics. To address this issue, the 2013 National Socioeconomic Survey was derived from the Indonesian Statistics Agency and analyzed using logistic regression. Research results showed factors that significantly affected the probability of children fall into absolute poverty are low education level of parents, mother and head of householdâ€™s employment status, location of residences in villages, and having more than one child. Policies on poverty alleviation have been implemented by the government. However, a more comprehensive effort particularly for family with children under-five needs to be taken into account.Â